2020
DOI: 10.5860/crl.81.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy and Cultural Context: Chinese English Language Learners’ Understandings of Information Authority

Abstract: Chinese international students are attending higher education institutions in the United States in ever-increasing numbers, and librarians must consider their cultural, sociopolitical, and linguistic backgrounds in information literacy instruction. This exploratory study examines how Chinese international students at a public American university describe, understand, and interpret information literacy concepts, such as authority, through qualitative vignettes and in-depth interviews. The findings of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Each social setting has a unique cultural, institutional, and historical context that influences how people make credibility judgments (Limberg et al, 2012; Mansour & Francke, 2017). Research has shown that cultural understandings of information authority and previous life experiences can also affect international students’ assessment of information credibility (Crist & Popa, 2020; Rodriguez, 2014). For example, Chinese international students may consider the reputation and rankings of an institution (Rodriguez, 2014) or teachers (Crist & Popa, 2020) as the authority, which might not hold true in other sociocultural contexts.…”
Section: International Students and Online Informationmentioning
confidence: 99%
“…Each social setting has a unique cultural, institutional, and historical context that influences how people make credibility judgments (Limberg et al, 2012; Mansour & Francke, 2017). Research has shown that cultural understandings of information authority and previous life experiences can also affect international students’ assessment of information credibility (Crist & Popa, 2020; Rodriguez, 2014). For example, Chinese international students may consider the reputation and rankings of an institution (Rodriguez, 2014) or teachers (Crist & Popa, 2020) as the authority, which might not hold true in other sociocultural contexts.…”
Section: International Students and Online Informationmentioning
confidence: 99%
“…Library scholarship that examines authority has followed several patterns. Some recent publications accept the Framework's definition and employ it to suggest effective teaching methods (Dudley, 2020;Foskey & Roper, 2020;Heffernan, 2020;O'Neill, 2021;Pullman, 2018;Ward, 2022;White, 2019) or conduct research on students' understanding of authority (Crist & Popa, 2020;Rosenzweig et al, 2020). Others, however, grapple directly with the concept of authority itself.…”
Section: Authority In Library Scholarshipmentioning
confidence: 99%
“…Literasi digital memiliki peran yang sangat penting dalam mendukung pengambilan keputusan yang tepat dan meningkatkan pengetahuan (Crist & Popa, 2020;Reddy et al, 2020). Bahkan, Fukuyama (2018) menegaskan bahwa literasi digital telah menciptakan nilai baru dan kini menjadi pilar dalam pengambilan keputusan dan pembuatan kebijakan di berbagai institusi dan perusahaan.…”
Section: Pendahuluanunclassified
“…Menurut pandangan Crist & Popa, (2020), literasi digital lebih dari sekadar memberikan keterampilan teknis, literasi digital juga memberikan manfaat bagi masyarakat dengan membekali mereka dengan kemampuan berkomunikasi secara efektif dan berpikir kritis dalam menyelesaikan masalah. Dengan kemampuan ber-literasi yang baik (Sharma et al, 2016), masyarakat diharapkan mampu meraih peluang dan berkolaborasi secara lebih efisien.…”
Section: Pendahuluanunclassified